Making of unintentional injury pyramid chart by age group in Japan. (1st March 2011) - Uchiyama, Y; Tanaka, T; Ishii, H; Matsuda, H
Abstract : Background: The purpose of this study was to make Japanese unintentional injury pyramid chart indicating the relation between injury death, hospitalisations and practice visits by age group for consider the feature of unintentional injury in Japan. Methods: Mortality data for unintentional injuries available from Vital Statistics of Japan and the patient survey in 2008 were used. Results: In 2008, the mortality for unintentional injury was 13.2 per 100 000 populations under 1 year old. Assuming injury death was one, the hospitalisations were 33 and practice visits were 2028. Among 1–4 year olds, 3.8 and 1: 110: 11 196. Among 5–14 year olds, 2.1 and 1: 218: 20, 211. Among 15–24 year olds, 8.2 and 1: 102: 2869. Among 25–34 year olds, 7.0 and 1: 78: 2215. Among 35–44 year olds, 8.4 and 1: 63: 1691. Among 45–54 year olds, 13.2 and 1: 47: 1, 080. Among 55-64 year olds, 22.4 and 1: 38: 653. Among 65–74 year olds, 44.8 and 1: 31: 349. Over 75 year olds, 159.3 and 1: 24: 101. Conclusions: Though the injury pyramid chart is useful as an index for enlightenment of injury prevention, there are some features by age groups. Therefore, it is necessary to analyse injury data including the mortality, the hospitalisations, practice visits comprehensibly, particularly in children and seniors for effective injury prevention.